Lifestyle Medicine in Clinical Practice — Integrating the Six Pillars for Better Health Outcomes - Robak, Michał; Bajkacz, Agnieszka; Dudziński, Maciej; Kusy, Bartłomiej; Płonka, Marcin; Różańska, Martyna (Quality in Sport, 2025)
Background: Lifestyle Medicine is an evidence-based approach that helps prevent and treat chronic diseases through modifications in daily habits. It includes key pillars: nutrition, physical activity, restorative sleep, avoidance of harmful substances, stress management, and social relationships. These interconnected domains play a critical role in promoting long-term health and well-being. Aim: To introduce the core principles of Lifestyle Medicine and present practical, evidence-based strategies for integrating them into routine patient care. Methods: This narrative review synthesizes current research findings and official guidelines from leading health organizations, such as World Health Organization and the American College of Lifestyle Medicine. Literature review was conducted using PubMed database.